FRAMEWORK FOR INTEGRATION OF VERTICAL PUBLIC HEALTH SUPPLY CHAIN SYSTEMS: A CASE STUDY OF NIGERIA - Maliyogbinda, Jibrailu; Tijjani , Usman (International Journal of Supply Chain Management, 2022)
FRAMEWORK FOR INTEGRATION OF VERTICAL PUBLIC HEALTH SUPPLY CHAIN SYSTEMS: A CASE STUDY OF NIGERIA Jibrailu L. Maliyogbinda, Sr and Usman Tijjani FRAMEWORK FOR INTEGRATION OF VERTICAL PUBLIC HEALTH SUPPLY CHAIN SYSTEMS: A CASE STUDY OF NIGERIA Jibrailu L. Maliyogbinda, Sr., 1 (BPharm, MBA, MIAD, MSc., MCIPS, PMP), # 3 MAJILO Street, Plot 563 Kubwa Ext. 2 (Relocation), Abuja-FCT, Nigeria. jibrailu@outlook.com, +234(0)809 599 9911 Usman Tijjani BSc. (Hons), MSc, MPH., Consultant of Monitoring, Evaluation & Learning (MEL) of Public Health Programs, # 8., Guava Road, Unguwan Dosa, Kaduna, Kaduna state. tijjaniusman100@gmail.com. +234(0)8065554283. Abstract Purpose: The purpose of this research study is to explore the opinion of public health supply chain experts in Nigeria on the modalities for the integration of vertical public health supply chain systems and to proffer a practical and systematic contextual framework for achieving a seamless integration of vertical supply chain systems in the public health sector. Methodology: This research study was a qualitative thematic content analysis of the views of fifteen respondents from the six geopolitical zones of Nigeria using an interpretive philosophical approach through the theoretical lens of constructivism. Respondents in this study had at least three years' experience in the management of pharmaceuticals and other health products in one or more public health intervention programs including HIV/AIDS, Tuberculosis & Leprosy, Malaria, Reproductive Health and Family Planning, Vaccines and Immunisation, Neglected Tropical Diseases and Essential Medicines Programmes. Findings: The findings of the research study were based on a holistic and comprehensive approach that included cost benefit analysis, justifications, and circumstances for viable integration of vertical public health supply chain systems, which are relationship management, information integration, product integration and coordination called the four modalities/dimensions/practices of supply chain integration and need to exist in a continuum driven by purposeful leadership. Even though the data collected through semi-structured interviews did not allow for differing views among respondents, the opportunity to freely express one's opinion resulted in a rich data. Going forward, the government and its development partners need to demonstrate political and financial commitment to the course of integrating vertical public health supply chain systems in the country. The research study for the first time presented a practical and contextual framework for the seamless integration of public health supply chain systems, especially for low- and medium-income countries. Unique contribution to theory, practice, and policy: This research study contributes to the integration of vertical public health supply chain system in Nigeria and proffer practical and systematic contextual framework for achieving a seamless integration of vertical supply chain systems in the public health.